If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1Y + Z = 3 Solving X + -1Y + Z = 3 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add 'Y' to each side of the equation. X + -1Y + Y + Z = 3 + Y Combine like terms: -1Y + Y = 0 X + 0 + Z = 3 + Y X + Z = 3 + Y Add '-1Z' to each side of the equation. X + Z + -1Z = 3 + Y + -1Z Combine like terms: Z + -1Z = 0 X + 0 = 3 + Y + -1Z X = 3 + Y + -1Z Simplifying X = 3 + Y + -1Z
| x-2/12=5/6 | | -1+y/8=15 | | 4x+8y+20= | | 3x^3-7.5x^2-32=0 | | -3+m/9=10 | | -10=-2+1/2d | | 158-3x=24x+20 | | 6-7x=51-42x | | X-Y+C=3 | | 2x^2-1=9 | | 76-2x=10x-2x | | 12x-4=4x-3 | | 3y+4=7-4y | | 2(2x+7)+3(x+2)=5(x-1)-1 | | 6x-8=2x+32 | | 1+8x=22x+x | | 8y-2=7+6y | | (2x/3)=(4/7) | | 9x-1+8z-7x+z=0 | | 2x^2+17xy+8y^2= | | 8(2x+1)=11x+53+5x | | -x+9=x-21 | | x+9=x-21 | | x/9=40/5 | | 2x+1=x^2-14x+49 | | 5x+46=x^2+16x+64 | | 36=2x*3y | | x^2+4x+4+14x+28+45=0 | | 7(x-2)=-6+9x | | 3x^2-7-6=0 | | x+12=3x+20 | | -5y+8/3=5/4+4y+2 |